Age, Weight, and Menstruation as Determinants of Blood Haemoglobin Levels in Adolescent Girls - Pujianto, Tutut; Santoso, Puguh (Jurnal Keperawatan Profesional (KEPO), 2025)
Adolescent girls are a group with a risk of experiencing a decrease in Hb, because every month they experience menstruation. Menstruation results in a lot of blood, the loss of blood is synonymous with the loss of red blood cells. The reduced number of red blood cells results in the ability of the blood to carry oxygen into the body. This study aimed to prove whether age, weight and menstruation (predictor variable) affect blood Hb (response variable). The results of the study was also to determine which predictor variable has a dominant influence on the response variable. This research was carried out at SMPN 1 Ngancar, Kediri Regency, developing a cross-sectional design of 80 students, subjects were randomly selected and willing to be a sample. The predictor variable consists of age (x1), weight (x2) and menstrual status (x3), while the response variable is blood haemoglobin (y). The results of the study determined that the predictor variables that affected the subjects' blood Hb levels were age and menstruation. Menstruation is a more dominant variable than the age of the subject. Subjects should increase awareness in consuming foods high in iron, as well as Fe supplements, especially during menstruation.